Operating system network security enhancement scheme based on trusted storage - Longyun Qi; Xiaoliang Lv; Lianwen Sun; Tianle Yao; Jianye Yu; Lei Wang (Intelligent and Converged Networks, 2023)
Data storage security has become the core of many network security issues. In order to achieve trusted storage and trusted measurement of network community data, this paper proposes a secure storage model based on trust extension for existing trusted storage technologies. In the process of document encryption, the key information is encrypted as well as decentralized stored by optimizing the ciphertext inverted index structure and update policy to ensure the security of index information. In the process of user access control mechanism, SAML and XACML are used in combination with role-based access control in order to achieve flexible and efficient authorization and access control. In the process of result query, ontology technology is introduced to better express the user’s query intention and improve the query accuracy. A large number of experiments demonstrate the effectiveness and feasibility of the scheme.